2021
DOI: 10.1037/spy0000266
|View full text |Cite
|
Sign up to set email alerts
|

A history of parent involvement in organized youth sport: A scoping review.

Abstract: A fundamental step in describing a research field is the review and synthesis of accumulated knowledge. Multiple qualitative reviews have been conducted over the last decade to provide a summary and commentary on the growing literature in the area of youth sport parenting.However, these reviews have focused on contemporary findings in the field, largely ignoring work in the area that began in the late 1960s. In light of this under-discussed history, there remains a need to highlight the historical foundations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0
6

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 127 publications
(234 reference statements)
1
29
0
6
Order By: Relevance
“…Unfortunately, however, parents are often perceived as a source of stress for coaches, not least because parents may question coaches and be perceived to interfere with training and competitions (e.g., Gould et al, 2008). Over the last decade, there has been increasing research conducted exploring parental involvement in sport (e.g., Dorsch et al, 2021), with a range of strategies and techniques being suggested to facilitate positive parentcoach relationships (e.g., Knight & Gould, 2016;Smoll et al, 2011). Such strategies have typically focused upon how coaches could interact and communicate with parents with limited consideration being given to how coaches themselves may be "upskilled" to better manage and navigate interactions.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, however, parents are often perceived as a source of stress for coaches, not least because parents may question coaches and be perceived to interfere with training and competitions (e.g., Gould et al, 2008). Over the last decade, there has been increasing research conducted exploring parental involvement in sport (e.g., Dorsch et al, 2021), with a range of strategies and techniques being suggested to facilitate positive parentcoach relationships (e.g., Knight & Gould, 2016;Smoll et al, 2011). Such strategies have typically focused upon how coaches could interact and communicate with parents with limited consideration being given to how coaches themselves may be "upskilled" to better manage and navigate interactions.…”
Section: Discussionmentioning
confidence: 99%
“…Within the last 50 years, there has been growing interest in parental involvement in organised youth sport contexts (see Dorsch et al, 2021 for a historical scoping review). Researchers have provided an in-depth understanding of parents' roles in children's sport socialisation (e.g., Dorsch et al, 2009), parent's influence on child outcomes in sport (e.g., Atkins et al, 2013), coaches and young athletes' perceptions of parental involvement in sport (e.g., Knight et al, 2011), parent-child interactions (e.g., Thrower et al, 2022), and factors influencing parental involvement at both individual and environmental levels (e.g., Harwood & Knight, 2009).…”
Section: Evaluating the 'Optimal Competition Parenting Workhop' Using...mentioning
confidence: 99%
“…However, the extent to which young people obtain these benefits is largely contingent upon sustained involvement and the support they receive when participating ( Knight, Berrow, & Harwood, 2017 ). One particularly important source of support are parents ( Dorsch, Wright, et al, 2021 ). Parents play a key role in socialising children into sport ( Coakley, 2006 ; Elliott, Bevan, & Litchfield, 2020 ), influencing their motivational behaviour ( Keegan, Harwood, Spray, & Lavallee, 2009 ), and supporting their psychosocial development ( Knight, Neely, & Holt, 2011 ).…”
Section: Introductionmentioning
confidence: 99%